Exhibiting Agendas: Anthropology at the Redpath Museum (1882-99) - Lawson, Barbara (Anthropologica, 2022)
McGill University’s Redpath Museum is considered here for its significance as a site of Canadian scientific endeavour and a natural history museum of national importance, which devoted a small but prominent gallery to displays of archaeological and ethnological objects. A closer examination of collections and museological practice at the Redpath Museum during the closing decades of the 19th century may serve to illuminate factors influencing the advent of professional anthropology in Canada, typically submerged in the wake of presentist interpretations of the discipline’s past.